Characterization of Active Sites in Solid Oxide Fuel Cell Composite Cathode through Oxygen Isotope Labeling Combined with Three-Dimensional Microstructural Analysis by Focused Ion Beam – Scanning Electron Microscopy. (10th July 2019) - Nagasawa, Tsuyoshi; Shimura, Takaaki; Shikazono, Naoki; Hanamura, Katsunori
Abstract : A new SOFC electrode characterization technique combining active sites imaging by oxygen isotope labeling and three-dimensional (3D) microstructural observation by focused-ion beam-scanning electron microscopy (FIB-SEM) is carried out. A YSZ electrolyte-supported cell with Ni/YSZ anode and LSM/YSZ cathode was operated at 700℃ supplied with 18 O2 under a constant current, then the cell was quenched by water-cooled helium gas impinging jet. The 3D microstructure of the quenched cathode was obtained by orthogonally-aligned FIB-SEM. During the FIB-SEM observation, 18 O concentration on the milled surface was measured by secondary ion mass spectroscopy (SIMS). As a result, 3D-microstructure of the LSM/YSZ cathode with a 2D- 18 O concentration mapping in the intermediate plane of the characterized volume was obtained. Finally, the relationship between 18 O concentration distribution and 3D-microstructure of the cathode was discussed.